Numerical investigation of lift-force generation on a moving circular cylinder in a uniform flow driven by longitudinal vortex. (November 2018) - Hemsuwan, Withun; Sakamoto, Kasumi; Takahashi, Tsutomu
Abstract: A new concept for generating a steady lift force on a circular cylinder in a uniform flow is presented. A strip-plate is placed behind the upstream cylinder in a cruciform arrangement with a suitable gap distance, s, between them to employ the longitudinal vortex. The circular cylinder is driven by the aerodynamic effects of the longitudinal vortex induced steady lift force. In this paper, the system was examined using the unsteady Reynolds-averaged Navier–Stokes (URANS) approach with the shear-stress-transport (SST) k- ω model and adaptive wall function in the commercial CFD software, SC/Tetra. Two conditions were simulated for comparisons; i.e., the stationary-isolated cylinder and the parallel moving cylinder with a downstream strip-plate. Two effective parameters of the presented mechanism were investigated as the velocity ratio, VR, and the gap distance ratio, s/d . The wind-tunnel investigation in our laboratory was used for validation as well as the experiments, and other numerical results in the literature of the stationary-isolated cylinder, and the similar cases of flow over a free-end cylinder were employed for discussion. Three-dimensional structure of the longitudinal vortex and the limiting streamlines around the cylinder surfaces were numerically visualized. Distributions of the circumferential pressure and driving force coefficients were continuously evaluated along the cylinder axis. Highlights: URANS results were validated with the experimental data. Longitudinal vortex structure was visualized and provided the supplementary movies. Limiting streamlines showed the flow patterns around the cylinder surface. Aerodynamic driving forces along the cylinder length were continuously evaluated.